Application Of The Sol-Gel Hydroxhapatite Synthesis Method From Green Clam Shell - Edahwati, Luluk; Sutiyono, Sutiyono; Ikaputri, Aninda; Nur Fuadzi, Moh (Publisher Cv. Inara, 2023)
Hydroxyapatite is the main mineral that makes up bones and teeth so that it has a level of similarity with the mineral parts of bones and can be used as an alternative bone substitute material. As an alternative material for bone substitution, hydroxyapatite has a fairly high economic value and is still dominated by imports from foreign countries. In an effort to reduce the level of imports of hydroxyapatite, research was carried out on green mussel shells as a source of calcium for the synthesis of hydroxyapatite. The synthesis of hydroxyapatite was carried out using the sol-gel method with raw materials for calcium precursors obtained from green mussel shells and varied concentrations of phosphoric acid (0.1 M, 0.5 M, 1 M; 1.5 M; and 2 M). Based on the analysis of the hydroxyapatite product produced using Atomic Absorption Spectrophotometry analysis, it was found that the ratio of Calcium-Phosphate (Ca/P) for H3PO4 concentrations was 0.1 M, 0.5 M, 1 M; 1.5M; and 2 M respectively by 1.73; 1.70; 1.67; 1.63; and 1.61. In addition, based on the results of the Fourier Transform Infra Red analysis, a random sample also found a Ca-O group; PO43; and OH- which is the main group of Hydroxyapatite and from SEM analysis the crystal morphology is known to be spherical, uneven and agglomerated so that in this study the synthesis of Hydroxyapatite using the sol-gel method was successfully carried out..